2022
DOI: 10.3390/jcm11206156
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Prenatal Management of Congenital Adrenal Hyperplasia

Abstract: Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive diseases that may cause cortisol insufficiency together with other hormonal alterations. The most common form is 21-hydroxylase deficiency, in which the lack of pituitary negative feedback causes an increase in ACTH and adrenal androgens. Classical forms of CAHs can lead to severe adrenal failure and female virilization. To date, the appropriate management of pregnant CAH patients is still debated regarding appropriate maternal therapy modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 99 publications
0
10
0
1
Order By: Relevance
“…The concern arises regarding the continued use of DEX in unaffected females and affected male fetuses, as animal studies suggest that long duration treatment with DEX can potentially lead to adverse effects on the developing fetal brain, highlighting the need to stop the DEX therapy as soon as it is deemed to be clinically unnecessary 47 . The dose regimen given to mothers at risk of possible virilization is 20 μg/kg/day, based on the maternal pre‐pregnancy weight administered in three divided doses to receive a total value of about 1.5 mg/day 4,48 . In 2021, Stachanow et al 49 .…”
Section: Prenatal Diagnosis and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The concern arises regarding the continued use of DEX in unaffected females and affected male fetuses, as animal studies suggest that long duration treatment with DEX can potentially lead to adverse effects on the developing fetal brain, highlighting the need to stop the DEX therapy as soon as it is deemed to be clinically unnecessary 47 . The dose regimen given to mothers at risk of possible virilization is 20 μg/kg/day, based on the maternal pre‐pregnancy weight administered in three divided doses to receive a total value of about 1.5 mg/day 4,48 . In 2021, Stachanow et al 49 .…”
Section: Prenatal Diagnosis and Managementmentioning
confidence: 99%
“…As with any treatment, treating the developing fetus with DEX is not without risk, as studies have demonstrated that there can be possible maladaptive effects on the fetus's metabolism and intellect 53 . This prompts the following question: “Do the benefits of using steroid therapy to prevent fetal virilization in utero outweigh the risks?” This question is critical to consider as while steroid intervention can defer virilization and prevent the need for genital feminization surgery, complications related to the therapy can cause long‐standing physical and mental complications to both mother and baby, considered to be substantially worse off than genital masculinization 48 …”
Section: Prenatal Diagnosis and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Como o NCCAH não é o alvo primário da triagem neonatal e raramente é detectado por essa estratégia, a verdadeira prevalência desse distúrbio mais leve não é clara. Tem uma prevalência de 1:300 a 1:27 em diferentes grupos étnicos, tornando potencialmente a 21-OHD uma das doenças autossômicas recessivas mais comuns em humanos (CHATZIAGGELOU A, et al, 2019; CLAAHSEN- CERA G, et al, 2022).…”
Section: Hac Clássica E Não Clássicaunclassified
“…For patients with CAH who desire pregnancy, prepregnancy counseling is essential so that their partner can undergo testing and subsequently assess the risk of having a fetus with CAH. 44 Assisted reproductive technology and preimplantation genetics offer couples at risk of having a fetus with CAH the opportunity to transfer an unaffected embryo. 45…”
Section: Fertilitymentioning
confidence: 99%